Factors for Avoiding Counseling Despite Experiencing Cognitive Impairment in South Korea - In Cheol Hwang; Hong Yup Ahn (Alzheimer Disease & Associated Disorders, 2026)
This study examined factors associated with not seeking counseling among 46,156 Korean adults who experienced cognitive impairment in the past year, using data from the 2024 Korea Community Health Survey. Only 8.1% sought counseling. Age-stratified logistic regression showed that counseling-seeking increased with greater disruption of daily activities. Alcohol consumption consistently predicted not seeking counseling across all age groups, while depression was associated with greater counseling seeking. Lower economic status generally increased counseling seeking, though financial barriers limited help-seeking among older adults. Among middle-aged adults, being unmarried and having hypertension were also linked to higher counseling seeking. These findings suggest the need for age-specific strategies to encourage early help-seeking for cognitive impairment.